Strategy For A Large Scale Introduction Of Solar Energy In Central Asia - A. Rödl; M. Kaltschmitt; H. Schaumburg (MANAS: Journal of Engineering)
In spite of the significant need for energy and the large power of solar radiation (insolation) available in Central Asia the use of solar energy is still in a starting phase. In this paper a strategy is lined out how this deficit may be overcome, start-ing from a large number of affordable small and medium-sized photovoltaic solar plants. Details for various types of multi-purpose and dedicated solar plants are explained. Investment costs may be significantly lowered by the assembly of solar panels and the production of connectors, wiring and special accumulators within Central Asia. PV solar panels produce a much lower amount of greenhouse gases than Diesel generators resulting in a significant contribution to cli-mate change mitigation.